2011
DOI: 10.1063/1.3517494
|View full text |Cite
|
Sign up to set email alerts
|

Rotational spectroscopy and molecular structure of the 1-chloro-1-fluoroethylene-acetylene complex

Abstract: Guided by ab initio calculations, Fourier transform microwave spectra in the 6-21 GHz region are obtained for seven isotopomers of the complex formed between 1-chloro-1-fluoroethylene and acetylene. These include the four possible combinations of (35)Cl- and (37)Cl-containing CH(2)CClF with the most abundant acetylene isotopic modification, HCCH, and its H(13)C(13)CH analogue, as well as three singly substituted deuterated isotopomers. Analysis of the spectra determines the rotational constants and additionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 23 publications
3
31
0
Order By: Relevance
“…1). Three are qualitatively similar to their HCCH counterparts [2]: with the acid hydrogen bonding to the F atom in the ethylene subunit and forming a secondary interaction with the H atom cis to the F atom [structure (a)]; a second structure with a hydrogen bond to the same F atom, but with the donor approaching from a different angle and with no secondary interaction [structure (b)]; and third, the acid hydrogen bonding to the Cl atom with a secondary interaction involving the H atom in the cis position [structure (c)]. It is interesting to note that relative energies of structures (b) and (c) are reversed as compared to the corresponding minima for CH 2 CClF-HCCH.…”
Section: Ab Initio Calculationssupporting
confidence: 61%
See 3 more Smart Citations
“…1). Three are qualitatively similar to their HCCH counterparts [2]: with the acid hydrogen bonding to the F atom in the ethylene subunit and forming a secondary interaction with the H atom cis to the F atom [structure (a)]; a second structure with a hydrogen bond to the same F atom, but with the donor approaching from a different angle and with no secondary interaction [structure (b)]; and third, the acid hydrogen bonding to the Cl atom with a secondary interaction involving the H atom in the cis position [structure (c)]. It is interesting to note that relative energies of structures (b) and (c) are reversed as compared to the corresponding minima for CH 2 CClF-HCCH.…”
Section: Ab Initio Calculationssupporting
confidence: 61%
“…We have interpreted these results in terms of changes in F atom nucleophilicity caused by the differing degrees of substitution and the importance of attaining a balance between electrostatic and steric effects [1]. More recently, we have extended this work to consider not only fluorine, but also chlorine substitution in a study of the 1-chloro-1-fluoroethylene-acetylene complex, where we found that the intermolecular interactions in CH 2 CClF-HCCH were, within experimental uncertainty, indistinguishable from those of its 1,1-difluoroethylene counterpart, suggesting identical effects for geminal substitution of hydrogen in vinyl fluoride by either fluorine or the less electronegative, more polarizable chlorine [2]. This was at odds with theoretical predictions.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…We have recently extended this work to consider not only fluorine, but also chlorine substitution [19], and we also wish to investigate the effects of the increased degree of fluorine substitution that can occur in larger olefins. A complex formed between a protic acid and 2,3,3,3-tetrafluoropropene (TFP), when compared with the analogous vinyl fluoride or 1,1-difluoroethylene species, would show the consequences of replacing a hydrogen atom or a fluorine atom, respectively, by the -CF 3 moiety.…”
Section: Introductionmentioning
confidence: 99%